Parosmia, Dysgeusia, and Tongue Features Changes in a Patient with Post-Acute COVID-19 Syndrome - Aliaa Abdelmoniem Bedeir Eita (Hindawi Limited, 2021)
Coronavirus disease 2019 (COVID-19) is the pandemic of major global concern that has been causing several tragic events ever since December 2019. Infection with COVID-19 varies from being asymptomatic or mild with general unwellness to severe with difficulty in breathing and even mortality. Recently, several reports signified the persistence of symptoms or the development of new ones for weeks or months after the virus has gone, the so-called "post-acute COVID-19 syndrome." This article presents a 31-year-old female with post-acute COVID-19 syndrome showing parosmia, dysgeusia, and tongue feature changes as simultaneous newly developed manifestations after the viral clearance. Follow-up revealed complete remission of manifestations after one month. Post-acute COVID-19 syndrome can show oral manifestations. Despite the lack of evidence regarding the etiology, risk factors, and consequences of post-COVID-19 syndrome, it is important to monitor COVID-19 survivors to avoid complications during their recovery period.